A área central e sua dinâmica:uma discussão - Vitor Ribeiro Filho (Sociedade & Natureza)
This document aims to understand the Central Area as it is nowadays as well as its late dynamics. During the twentieth century, that area has faced several and significant trasformations, which have affected the whole town, causing its commercial and service activities spatial structures to modify. Admist such process, one can claerly see a redesigning of the core, which no longer mopolizes commercial or service activities, sharing them with the other non-central areas from the town.